Equilibrium in the Pricing of Capital Assets, Risk-Bearing Debt Instruments, and the Question of Optimal Capital Structure - Haugen, Robert A.; Pappas, James L. (Journal of Financial and Quantitative Analysis, 1971)
Robert A. Haugen, James L. Pappas, Equilibrium in the Pricing of Capital Assets, Risk-Bearing Debt Instruments, and the Question of Optimal Capital Structure, The Journal of Financial and Quantitative Analysis, Vol. 6, No. 3 (Jun., 1971), pp. 943-953